Cloning of beta-xylosidase gene from aspergillus niger - Muhammad Zaidi, Nor Fadzilah; Md. Illias, Rosli (2007)
Filamentous fungi are known to be efficient producers of xylanolytic enzymes, and most commercial xylanolytic preparations are obtained from fermentations of Aspergillus or Trichoderma species. Î²-xylosidase genes from Aspergillus niger was amplified using Polymerase Chain Reaction. Î²-xylosidase gene in Aspergillus niger contains an open reading frame of 2,412 nucleotides which show high similarity to Aspergillus awamori xyl mRNA for Î²-xylosidase (Accession Number: AB 154359) . The gene encoded 804 amino acid sequence of Î²-xylosidase. Amino acid analysis shows 99% identities to Î²-xylosidase from Aspergillus awamori.